Chassis dynamometer for electric two wheelers - Muhammad Hadi, Hassan; Syazwana, Sapee; Daing Mohamad Nafiz, Daing Idris; Ahmad Fitri, Yusop; F., Basrawi; Azri Hizami, Rasid (EDP Sciences, 2018)
In recent years, electric two-wheelers are emerging as one of the alternatives to improve the sustainability of transportation energy and air quality, especially in urban areas. Although electric two-wheeler motorcycles are environmentally friendly, they underperform compared with gasoline two-wheelers in many respects, particularly in speed and cruise distance between refuelling and recharging. Therefore, the engine development program can be done with a dynamometer. Variables such as the shape of torque and power curves can be analyzed. Hence, this project is aimed to develop a chassis dynamometer that can be used to measure mechanical power, speed and torque, and provide a controllable load to the electric motorcycle being tested. The prototype of chassis dynamometer for electric motorcycle had been developed and performance of the chassis dynamometer was tested by using an electric bicycle to emulate the basic performance requirements of an electric motorcycle which consist of maximum speed, driving range and acceleration.